Estimation of Population Size of Dentaria Enneaphyllos in the Vicinity of the Bełchatów Brown Coal Mine and the Attempt of Its Metaplantation - Kurowski, Józef K.; Koczywąs, Ewelina; Pieńkowski, Michał (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
The impact of anthropopressure on the flora in the vicinity of the Bełchatów Brown Coal Mine in Central Poland has been substantially strong. Consequently, certain changes in habitat conditions have been observed, leading to a decline in particular species stands. Mechanical damage, as well as the mine and power plant expansion have contributed to further species decline in the area. Ex situ conservation, e.g. metaplantation from native to secondary localities seems an efficient method of ensuring the species survival in the local flora. One of the species is to be found in Wola Wydrzyna (under the Forest District Administration of Bełchatów) is Drooping Bittercress Dentaria enneaphyllos. Its population was first recorded in the area in 1979. However, since 2009 the forest complex has undergone a regular expansion of the Bełchatów Brown Coal Mine. The forest area is to be utilised for the future Szczerców coal deposit. Therefore, in 2000 the method of Dentaria enneaphyllos metaplantation was applied.